Synthesis, In Vitro and In Vivo Evaluation of the N-ethoxycarbonylmorpholine Ester of Diclofenac as a Prodrug - Jamal A. Jilani; Nasir M. Idkaidek; Karem H. Alzoubi (MDPI AG, 2014)
The N-ethoxycarbonylmorpholine moiety was evaluated as a novel prodrug moiety for carboxylic acid containing drugs represented by diclofenac (1). Compound 2, the N-ethoxycarbonylmorpholine ester of diclofenac was synthesized and evaluated as a potential prodrug. The stability of the synthesized prodrug was evaluated in solutions of pH 1 and 7.4, and in plasma. The ester's half lives were found to be 8 h, 47 h and 21 min in pH 1, pH 7.4 and plasma, respectively. Equimolar doses of diclofenac sodium and its synthesized prodrug were administered orally to a group of rabbits in a crossover study to evaluate their pharmacokinetic parameters. The prodrug 2 shows a similar rate and extent of absorption as the parent drug (1). The ulcerogenicity of the prepared prodrug was evaluated and compared with the parent drug. The prodrug showed less ulcerogenicity as detected by fewer number and smaller size of ulcers. In conclusion, the newly synthesized N-ethoxycarbonylmorpholine ester of diclofenac prodrug showed appropriate stability properties at different pHs, similar pharmacokinetic profile, and much less ulcerogenecity at the GIT compared to the parent drug diclofenac.